Photoluminescence properties of open and closed uranium compounds in non-aqueous media - Hashem, Emtithal (Trinity College (Dublin, Ireland). School of Chemistry, 2013)
Luminescence spectroscopy has been successfully applied to elucidate the photophysical properties of a family of uranium halides and pseudohalides, in two oxidation states (U IV and U VI) in non-aqueous media. The first example of the room temperature emission spectroscopy of uranium(IV) in non-aqueous media is reported and the limitations of the luminescence spectroscopic technique and the influence of fhe geometry on the photophysical properties were investigated. Such compounds were selected in order to avoid any possible quenching of the excited state, which may arise from an aromatic group or conjugated entities. Ligand centered charge transfer bands in the visible region were also important to avoid since they provide another quenching pathway.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin.